Solution to what? Global assessment of nature-based solutions, urban challenges, and outcomes - Meng Li; Roy P. Remme; Peter M. van Bodegom; Alexander P.E. van Oudenhoven (Landscape and Urban Planning, 2025)

When can we detect lianas from space? Toward a mechanistic understanding of liana‐infested forest optics - Marco D. Visser; Matteo Detto; Félicien Meunier; Jin Wu; Jane R. Foster; David C. Marvin; Peter M. van Bodegom; Boris Bongalov; Matheus Henrique Nunes; David Coomes; Hans Verbeeck; J. Antonio Guzmán Q; et al. (Ecology, 2025)
Lianas, woody vines acting as structural parasites of trees, have profound effects on the composition and structure of tropical forests, impacting tree growth, mortality, and forest succession. Remote sensing could offer a powerful tool for quantifying the scale of liana infestation, provided the availability of robust detection methods. We analyze the consistency and global geographic specificity of spectral signals—reflectance across wavelengths—from liana‐infested tree crowns and forest stands, examining the underlying mechanisms of these signals. We compiled a uniquely comprehensive database, including leaf reflectance spectra from 5424 leaves, fine‐scale airborne reflectance data from 999 liana‐infested canopies, and coarse‐scale satellite reflectance data covering 775 ha of liana‐infested forest stands. To unravel the mechanisms of the liana spectral signal, we applied mechanistic radiative transfer models across scales, establishing a synthesis of the relative importance of different mechanisms, which we corroborate with field data on liana leaf chemistry and canopy structure. We find a consistent liana spectral signal at canopy and stand scales across globally distributed sites. This signature mainly arises at the canopy level due to direct effects of more horizontal leaf angles, resulting in a larger projected leaf area, and indirect effects from increased light scattering in the near and short‐wave infrared regions, linked to lianas' less costly leaf construction compared with trees on average. The existence of a consistent global spectral signal for lianas suggests that large‐scale quantification of liana infestation is feasible. However, because the traits responsible for the liana canopy‐reflectance signal are not exclusive to lianas, accurate large‐scale detection requires rigorously validated remote sensing methods. Our models highlight challenges in automated detection, such as potential misidentification due to leaf phenology, tree life history, topography, and climate, especially where the scale of liana infestation is less than a single remote sensing pixel. The observed cross‐site patterns also prompt ecological questions about lianas' adaptive similarities in optical traits across environments, indicating possible convergent evolution due to shared constraints on leaf biochemical and structural traits.

Global increase of lianas in tropical forests - Manuela A. Rueda‐Trujillo; Michiel P. Veldhuis; Peter M. van Bodegom; Hannes P. T. de Deurwaerder; Marco Visser (Global Change Biology, 2024)
Lianas profoundly affect tropical forests dynamics, reducing productivity and carbon storage, which underscores the importance of monitoring change in their abundance in projecting the future of the global terrestrial carbon store. While increasing liana populations are documented within the Neotropics, the global consistency of these patterns is questioned, and remains to be determined. To evaluate pantropical trends in liana abundance comprehensively and quantitatively, we conducted a systematic literature review and meta‐analysis. This approach allowed us to synthesize data from published longitudinal studies examining liana trends across the tropics. We calculated standardized effect sizes and standard errors, and applied a Bayesian hierarchical meta‐analytic model to adjust for publication bias. Our analysis reveals an overall pan‐tropical increase in lianas abundance, occurring at an average rate of 1.7 ± 0.7 SE% per year (~10% to 24% per decade). This upward trend, confirmed to be robust against publication bias, extends beyond Neotropical regions, indicating a widespread phenomenon. Although a global trend of increasing liana abundance is evident, significant local variation exist, attributable to differences in life cycle stages, abundance metrics, forest successional stages, and biogeographical realms. Notably, increases in stem density of saplings and biomass of canopy lianas, especially in old‐growth forests, point to global climatic drivers and heightened turnover rates in tropical forests as factors promoting sustained liana growth in the canopy and clonal colonization in the understory. These trends suggest that the rise in liana abundance may not only persist but could also intensify under climate change. Considering both previous and current research on lianas, our findings confirm growing concerns about lianas' expanding impact on pan‐tropical carbon storage, highlighting their significant potential effect on global carbon dynamics.

CUGIC: The Consolidated Urban Green Infrastructure Classification for assessing ecosystem services and biodiversity - Joeri Morpurgo; Roy P. Remme; Peter M. Van Bodegom (Landscape and Urban Planning, 2023)

Soil Biota Adversely Affect the Resistance and Recovery of Plant Communities Subjected to Drought - Chenguang Gao; Peter M. van Bodegom; T. Martijn Bezemer; Michiel P. Veldhuis; Riccardo Mancinelli; Nadejda A. Soudzilovskaia (Ecosystems, 2023)
Climate change predictions indicate that summer droughts will become more severe and frequent. Yet, the impact of soil communities on the response of plant communities to drought remains unclear. Here, we report the results of a novel field experiment, in which we manipulated soil communities by adding soil inocula originating from different successional stages of coastal dune ecosystems to a plant community established from seeds on bare dune sand. We tested if and how the added soil biota from later-successional ecosystems influenced the sensitivity (resistance and recovery) of plant communities to drought. In contrast to our expectations, soil biota from later-successional soil inocula did not improve the resistance and recovery of plant communities subjected to drought. Instead, inoculation with soil biota from later successional stages reduced the post-drought recovery of plant communities, suggesting that competition for limited nutrients between plant community and soil biota may exacerbate the post-drought recovery of plant communities. Moreover, soil pathogens present in later-successional soil inocula may have impeded plant growth after drought. Soil inocula had differential impacts on the drought sensitivity of specific plant functional groups and individual species. However, the sensitivity of individual species and functional groups to drought was idiosyncratic and did not explain the overall composition of the plant community. Based on the field experimental evidence, our results highlight the adverse role soil biota can play on plant community responses to environmental stresses. These outcomes indicate that impacts of soil biota on the stability of plant communities subjected to drought are highly context-dependent and suggest that in some cases the soil biota activity can even destabilize plant community biomass responses to drought.

Global root traits (GRooT) database - Nathaly R. Guerrero‐Ramírez; Liesje Mommer; Grégoire T. Freschet; Colleen M. Iversen; M. Luke McCormack; Jens Kattge; Hendrik Poorter; Fons van der Plas; Joana Bergmann; Thom W. Kuyper; Larry M. York; Helge Bruelheide; et al. (Global Ecology and Biogeography, 2021)
Motivation Trait data are fundamental to the quantitative description of plant form and function. Although root traits capture key dimensions related to plant responses to changing environmental conditions and effects on ecosystem processes, they have rarely been included in large‐scale comparative studies and global models. For instance, root traits remain absent from nearly all studies that define the global spectrum of plant form and function. Thus, to overcome conceptual and methodological roadblocks preventing a widespread integration of root trait data into large‐scale analyses we created the Global Root Trait (GRooT) Database. GRooT provides ready‐to‐use data by combining the expertise of root ecologists with data mobilization and curation. Specifically, we (a) determined a set of core root traits relevant to the description of plant form and function based on an assessment by experts, (b) maximized species coverage through data standardization within and among traits, and (c) implemented data quality checks. Main types of variables contained GRooT contains 114,222 trait records on 38 continuous root traits. Spatial location and grain Global coverage with data from arid, continental, polar, temperate and tropical biomes. Data on root traits were derived from experimental studies and field studies. Time period and grain Data were recorded between 1911 and 2019. Major taxa and level of measurement GRooT includes root trait data for which taxonomic information is available. Trait records vary in their taxonomic resolution, with subspecies or varieties being the highest and genera the lowest taxonomic resolution available. It contains information for 184 subspecies or varieties, 6,214 species, 1,967 genera and 254 families. Owing to variation in data sources, trait records in the database include both individual observations and mean values. Software format GRooT includes two csv files. A GitHub repository contains the csv files and a script in R to query the database.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Traditional plant functional groups explain variation in economic but not size‐related traits across the tundra biome - H. J. D. Thomas; I. H. Myers‐Smith; A. D. Bjorkman; S. C. Elmendorf; D. Blok; J. H. C. Cornelissen; B. C. Forbes; R. D. Hollister; S. Normand; J. S. Prevéy; C. Rixen; G. Schaepman‐Strub; et al. (Global Ecology and Biogeography, 2019)
Aim Plant functional groups are widely used in community ecology and earth system modelling to describe trait variation within and across plant communities. However, this approach rests on the assumption that functional groups explain a large proportion of trait variation among species. We test whether four commonly used plant functional groups represent variation in six ecologically important plant traits. Location Tundra biome. Time period Data collected between 1964 and 2016. Major taxa studied 295 tundra vascular plant species. Methods We compiled a database of six plant traits (plant height, leaf area, specific leaf area, leaf dry matter content, leaf nitrogen, seed mass) for tundra species. We examined the variation in species‐level trait expression explained by four traditional functional groups (evergreen shrubs, deciduous shrubs, graminoids, forbs), and whether variation explained was dependent upon the traits included in analysis. We further compared the explanatory power and species composition of functional groups to alternative classifications generated using post hoc clustering of species‐level traits. Results Traditional functional groups explained significant differences in trait expression, particularly amongst traits associated with resource economics, which were consistent across sites and at the biome scale. However, functional groups explained 19% of overall trait variation and poorly represented differences in traits associated with plant size. Post hoc classification of species did not correspond well with traditional functional groups, and explained twice as much variation in species‐level trait expression. Main conclusions Traditional functional groups only coarsely represent variation in well‐measured traits within tundra plant communities, and better explain resource economic traits than size‐related traits. We recommend caution when using functional group approaches to predict tundra vegetation change, or ecosystem functions relating to plant size, such as albedo or carbon storage. We argue that alternative classifications or direct use of specific plant traits could provide new insights for ecological prediction and modelling.

Synthesis of ecosystem vulnerability to climate change in the Netherlands shows the need to consider environmental fluctuations in adaptation measures - P. M. van Bodegom; J. Verboom; J. P. M. Witte; C. C. Vos; R. P. Bartholomeus; W. Geertsema; A. Cormont; M. van der Veen; R. Aerts (Regional Environmental Change, 2013)

Highly consistent effects of plant litter identity and functional traits on decomposition across a latitudinal gradient - Marika Makkonen; Matty P. Berg; I. Tanya Handa; Stephan Hättenschwiler; Jasper van Ruijven; Peter M. van Bodegom; Rien Aerts (Ecology Letters, 2012)
Plant litter decomposition is a key process in terrestrial carbon cycling, yet the relative importance of various control factors remains ambiguous at a global scale. A full reciprocal litter transplant study with 16 litter species that varied widely in traits and originated from four forest sites covering a large latitudinal gradient (subarctic to tropics) showed a consistent interspecific ranking of decomposition rates. At a global scale, variation in decomposition was driven by a small subset of litter traits (water saturation capacity and concentrations of magnesium and condensed tannins). These consistent findings, that were largely independent of the varying local decomposer communities, suggest that decomposer communities show little specialisation and high metabolic flexibility in processing plant litter, irrespective of litter origin. Our results provide strong support for using trait‐based approaches in modelling the global decomposition component of biosphere‐atmosphere carbon fluxes.

Tundra in the Rain: Differential Vegetation Responses to Three Years of Experimentally Doubled Summer Precipitation in Siberian Shrub and Swedish Bog Tundra - Frida Keuper; Frans-Jan W. Parmentier; Daan Blok; Peter M. van Bodegom; Ellen Dorrepaal; Jurgen R. van Hal; Richard S. P. van Logtestijn; Rien Aerts (Ambio, 2012)

Going beyond limitations of plant functional types when predicting global ecosystem–atmosphere fluxes: exploring the merits of traits‐based approaches - P. M. Van Bodegom; J. C. Douma; J. P. M. Witte; J. C. Ordoñez; R. P. Bartholomeus; R. Aerts (Global Ecology and Biogeography, 2012)
Aim Despite their importance for predicting fluxes to and from terrestrial ecosystems, dynamic global vegetation models have insufficient realism because of their use of plant functional types (PFTs) with constant attributes. Based on recent advances in community ecology, we explore the merits of a traits‐based vegetation model to deal with current shortcomings. Location Global. Methods A research review of current concepts and information, providing a new perspective, supported by quantitative analysis of a global traits database. Results Continuous and process‐based trait–environment relations are central to a traits‐based approach and allow us to directly calculate fluxes based on functional characteristics. By quantifying community assembly concepts, it is possible to predict trait values from environmental drivers, although these relations are still imperfect. Through the quantification of these relations, effects of adaptation and species replacement upon environmental changes are implicitly accounted for. Such functional links also allow direct calculation of fluxes, including those related to feedbacks through the nitrogen and water cycle. Finally, a traits‐based model allows the prediction of new trait combinations and no‐analogue ecosystem functions projected to arise in the near future, which is not feasible in current vegetation models. A separate calculation of ecosystem fluxes and PFT occurrences in traits‐based models allows for flexible vegetation classifications. Main conclusions Given the advantages described above, we argue that traits‐based modelling deserves consideration (although it will not be easy) if one is to aim for better climate projections.

A frozen feast: thawing permafrost increases plant‐available nitrogen in subarctic peatlands - Frida Keuper; Peter M. van Bodegom; Ellen Dorrepaal; James T. Weedon; Jurgen van Hal; Richard S. P. van Logtestijn; Rien Aerts (Global Change Biology, 2012)
Many of the world's northern peatlands are underlain by rapidly thawing permafrost. Because plant production in these peatlands is often nitrogen ( N )‐limited, a release of N stored in permafrost may stimulate net primary production or change species composition if it is plant‐available. In this study, we aimed to quantify plant‐available N in thawing permafrost soils of subarctic peatlands. We compared plant‐available N ‐pools and ‐fluxes in near‐surface permafrost (0–10 cm below the thawfront) to those taken from a current rooting zone layer (5–15 cm depth) across five representative peatlands in subarctic Sweden. A range of complementary methods was used: extractions of inorganic and organic N, inorganic and organic N ‐release measurements at 0.5 and 11 °C (over 120 days, relevant to different thaw‐development scenarios) and a bioassay with Poa alpina test plants. All extraction methods, across all peatlands, consistently showed up to seven times more plant‐available N in near‐surface permafrost soil compared to the current rooting zone layer. These results were supported by the bioassay experiment, with an eightfold larger plant N ‐uptake from permafrost soil than from other N ‐sources such as current rooting zone soil or fresh litter substrates. Moreover, net mineralization rates were much higher in permafrost soils compared to soils from the current rooting zone layer (273 mg N m −2 and 1348 mg N m −2 per growing season for near‐surface permafrost at 0.5 °C and 11 °C respectively, compared to −30 mg N m −2 for current rooting zone soil at 11 °C). Hence, our results demonstrate that near‐surface permafrost soil of subarctic peatlands can release a biologically relevant amount of plant available nitrogen, both directly upon thawing as well as over the course of a growing season through continued microbial mineralization of organically bound N . Given the nitrogen‐limited nature of northern peatlands, this release may have impacts on both plant productivity and species composition.

Disturbance and resource availability act differently on the same suite of plant traits: revisiting assembly hypotheses - J. C. Douma; B Shipley; J.-P. M. Witte; R Aerts; P. M. van Bodegom (Ecology, 2012)
Understanding the mechanisms of trait selection at the scale of plant communities is a crucial step toward predicting community assembly. Although it is commonly assumed that disturbance and resource availability constrain separate suites of traits, representing the regenerative and established phases, respectively, a quantification and test of this accepted hypothesis is still lacking due to limitations of traditional statistical techniques. In this paper we quantify, using structural equation modeling (SEM), the relative contributions of disturbance and resource availability to the selection of suites of traits at the community scale. Our model specifies and reflects previously obtained ecological insights, taking disturbance and nutrient availability as central drivers affecting leaf, allometric, seed, and phenology traits in 156 (semi‐) natural plant communities throughout The Netherlands. The common hypothesis positing that disturbance and resource availability each affect a set of mutually independent traits was not consistent with the data. Instead, our final model shows that most traits are strongly affected by both drivers. In addition, trait–trait constraints are more important in community assembly than environmental drivers in half of the cases. Both aspects of trait selection are crucial for correctly predicting ecosystem processes and community assembly, and they provide new insights into hitherto underappreciated ecological interactions.

Global quantification of contrasting leaf life span strategies for deciduous and evergreen species in response to environmental conditions - A. E. E. van Ommen Kloeke; J. C. Douma; J. C. Ordoñez; P. B. Reich; P. M. van Bodegom (Global Ecology and Biogeography, 2012)
Aim Species with deciduous and evergreen leaf habits typically differ in leaf life span (LLS). Yet quantification of the response of LLS, within each habit, to key environmental conditions is surprisingly lacking. The aim of this study is to quantify LLS strategies of the two leaf habits under varying temperature, moisture and nutrient conditions, using a global database. We hypothesize that deciduous LLS reflects the length of the growing season, avoiding unfavourable conditions regardless of the cause. Evergreen species adjust to unfavourable periods and amortize lower net carbon gains over several growing seasons, with increasing LLS associated with increasingly short favourable versus unfavourable season lengths. Location Global. Methods Data on LLS and environmental variables were compiled from global datasets for 189 deciduous and 506 evergreen species across 83 study locations. Individual and combined effects of measures of seasonality of temperature, water and nutrient availability on length of the growing season and on LLS were quantified using linear mixed models. The best models for predicting LLS were obtained using Akaike's information criterion (AIC) and ΔAIC. Results The LLS of deciduous and evergreen species showed opposite responses to changes in environmental conditions. Under unfavourable conditions, deciduous LLS decreases while evergreen LLS increases. A measure of temperature alone was the best predictor of the growing season. The LLS of deciduous species was independent of environmental conditions after expressing LLS in relation to the number of growing seasons. Evergreen species, on the other hand, adjusted to unfavourable conditions by increasing LLS up to four growing seasons. Contrary to expectations, variation in LLS was best explained solely by temperature, instead of by combined measures of temperature, moisture and nutrient availability. Shifts in the photosynthesis to respiration balance might provide a physiological explanation. Main conclusions Temperature, and not drought or nutrient availability, is the primary driver of contrasting responses of LLS for different leaf habit types.

TRY – a global database of plant traits - J. KATTGE; S. DÍAZ; S. LAVOREL; I. C. PRENTICE; P. LEADLEY; G. BÖNISCH; E. GARNIER; M. WESTOBY; P. B. REICH; I. J. WRIGHT; J. H. C. CORNELISSEN; C. VIOLLE; et al. (Global Change Biology, 2011)
Plant traits – the morphological, anatomical, physiological, biochemical and phenological characteristics of plants and their organs – determine how primary producers respond to environmental factors, affect other trophic levels, influence ecosystem processes and services and provide a link from species richness to ecosystem functional diversity. Trait data thus represent the raw material for a wide range of research from evolutionary biology, community and functional ecology to biogeography. Here we present the global database initiative named TRY, which has united a wide range of the plant trait research community worldwide and gained an unprecedented buy‐in of trait data: so far 93 trait databases have been contributed. The data repository currently contains almost three million trait entries for 69 000 out of the world's 300 000 plant species, with a focus on 52 groups of traits characterizing the vegetative and regeneration stages of the plant life cycle, including growth, dispersal, establishment and persistence. A first data analysis shows that most plant traits are approximately log‐normally distributed, with widely differing ranges of variation across traits. Most trait variation is between species (interspecific), but significant intraspecific variation is also documented, up to 40% of the overall variation. Plant functional types (PFTs), as commonly used in vegetation models, capture a substantial fraction of the observed variation – but for several traits most variation occurs within PFTs, up to 75% of the overall variation. In the context of vegetation models these traits would better be represented by state variables rather than fixed parameter values. The improved availability of plant trait data in the unified global database is expected to support a paradigm shift from species to trait‐based ecology, offer new opportunities for synthetic plant trait research and enable a more realistic and empirically grounded representation of terrestrial vegetation in Earth system models.

Leaf habit and woodiness regulate different leaf economy traits at a given nutrient supply - Jenny C. Ordoñez; Peter M. van Bodegom; Jan-Philip M. Witte; Ruud P. Bartholomeus; Han F. van Dobben; Rien Aerts (Ecology, 2010)
The large variation in the relationships between environmental factors and plant traits observed in natural communities exemplifies the alternative solutions that plants have developed in response to the same environmental limitations. Qualitative attributes, such as growth form, woodiness, and leaf habit can be used to approximate these alternative solutions. Here, we quantified the extent to which these attributes affect leaf trait values at a given resource supply level, using measured plant traits from 105 different species (254 observations) distributed across 50 sites in mesic to wet plant communities in The Netherlands. For each site, soil total N, soil total P, and water supply estimates were obtained by field measurements and modeling. Effects of growth forms, woodiness, and leaf habit on relations between leaf traits (SLA, specific leaf area; LNC, leaf nitrogen concentration; and LPC, leaf phosphorus concentration) vs. nutrient and water supply were quantified using maximum‐likelihood methods and Bonferroni post hoc tests. The qualitative attributes explained 8–23% of the variance within sites in leaf traits vs. soil fertility relationships, and therefore they can potentially be used to make better predictions of global patterns of leaf traits in relation to nutrient supply. However, at a given soil fertility, the strength of the effect of each qualitative attribute was not the same for all leaf traits. These differences may imply a differential regulation of the leaf economy traits at a given nutrient supply, in which SLA and LPC seem to be regulated in accordance to changes in plant size and architecture while LNC seems to be primarily regulated at the leaf level by factors related to leaf longevity.

Trace Elements and Carbon and Nitrogen Stable Isotopes in Organisms from a Tropical Coastal Lagoon - A. A. Pereira; B. van Hattum; J. de Boer; P. M. van Bodegom; C. E. Rezende; W. Salomons (Archives of Environmental Contamination and Toxicology, 2010)

Plant responses to rising water tables and nutrient management in calcareous dune slacks - C. Bakker; P. M. Van Bodegom; H. J. M. Nelissen; W. H. O. Ernst; R. Aerts (Plant Ecology, 2006)

Gas Transport through the Root–shoot Transition Zone of Rice Tillers - T. T. Groot; P. M. van Bodegom; H. A. J. Meijer; F. J. M. Harren (Plant and Soil, 2005)

Effects of Ca- and Fe-rich Seepage on P Availability and Plant Performance in Calcareous Dune Soils - C. Bakker; J. Rodenburg; P. M. van Bodegom (Plant and Soil, 2005)

Effect of Straw Application on Rice Yields and Nutrient Availability on an Alkaline and a pH-neutral Soil in a Sahelian Irrigation Scheme - P. J. A. van Asten; P. M. van Bodegom; L. M. Mulder; M. J. Kropff (Nutrient Cycling in Agroecosystems, 2005)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)